Indels autossômicos e do cromossomo X em uma amostra da população do Rio Grande do Sul para possíveis aplicações forenses - Matte, Cecília Helena Fricke (2011)
Forensic genetics has developed in recent years due to its recognized importance in helping to solve a wide variety of criminal cases. This recognition has led to an increase in demand and hence the need to achieve results on samples that previously were not worked (due to the high degree of degradation) or inconclusive reports generated. The development of new methods of analysis and search for new genetic markers for forensic use is constant, and the biallelic markers of have shown great capacity for individualization and identification of a sample. We studied the frequencies of 47 autosomal and 13 X-chromosome insertiondeletion polymorphism (InDel) markers in a sample of 90 individuals in the population of Rio Grande do Sul state, to evaluate its applicability in forensic cases. Haplotype (DH) and haploid genetic (h) diversity, and information index (I) for X-chromosome markers, and observed heterozygosity (Ho), power of discrimination (PD), power of exclusion (PE) matching probability (MP), typical paternity index (TPI) and polymorphism information content (PIC) for autosomal markers, were calculated. For the 47 autosomes indels studied, the combined power of discrimination and the combined power of exclusion were 99.999999999999998956% and 99.64%, respectively. We did not observe a significant substructure in the population studied, and the global estimated admixture components for the sample were 72.35%, 18.10%, and 9.54% for European, Native American, and African DNA.